Caracterização química e avaliações biológicas da polpa dos frutos de Mauritia flexuosa L. f. (Arecaceae) do Cariri Cearense - NONATO, Carla de Fatima Alves (2018)
Fruit consumption is seen beyond the nutritional aspect, being correlated as important indicative for health promotion and disease prevention. The objective of this work was to obtain the chemical profile of the oil and the chloroform, ethyl acetate and ethanolic fractions of the fruit pulp of Mauritia flexuosa L. f. and to evaluate the antioxidant and antimicrobial capacities of these, as well as to analyze the bromatological composition of the pulp. The chemical composition of the oil and the fractions was determined by gas chromatography coupled to mass spectrometry (GC-MS) and high performance liquid chromatography with diode array detector (HPLC-DAD), respectively. The quantifications of total phenols and flavonoids of the fractions followed the methods Folin-Ciocalteu and complexation with aluminum chloride, respectively. The antioxidant capacity was verified by the sequestration of free radicals 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), iron reduction and chelation. The antimicrobial activity was determined by the minimum inhibitory concentration and by the modulatory action of aminoglycoside, beta-lactam and azolic antibiotics. The acidity, the saponification index and the refraction of the oil were characterized. The bromatological analyzes of moisture, total acidity, pH, proteins, total carbohydrates, ashes, lipids and vitamin C content were performed. In the chemical analyzes it was possible to quantify catechin, caffeic acid, rutin, orientin, quercetin, apigenin, luteolin and kaempferol of the fractions, as well as the major fatty acids of the oil, being these stearic acid, palmitic acid and oleic acid. Fractions exhibited moderate activity against Gram-positive bacteria and Candida strains, while the oil exhibited moderate activity only against Candida strains. As for modulation, fractions and oil presented synergistic and antagonistic effects on the analyzed antibiotics, where the most expressive synergic effect was obtained by the oil on cefotaxime versus Bacillus cereus. The acidity and the saponification index of the oil are within the limits established by the Brazilian Health Regulatory Agency. The pulp presented values of 21.68% of moisture, 12.29% of total acidity, 3.84 of pH, 38.77% of proteins, 29.82% of total carbohydrates, as well as values of 3.82% of ash, 5.91% of lipids and 60.53 mg / 100g of Vitamin C. The results suggest the potential use of fruits of M. flexuosa as antioxidant and antimicrobial therapy, in addition to their nutritional potential.